Detection of Beauvericin in the entomopathogenic fungus Beauveria bassiana by using polyclonal antibodies - ARBOLEDA-V., JORGE W.; DELGADO-B, FERNANDO; VALENCIA-J., ARNUBIO (Revista Colombiana de Entomología, 2004)
The entomopathogenic fungus Beauveria bassiana (Bals.) Vuillemin is a good tool for biological control of insects that attack economically important crops. This fungus produces a ciclohexadepsipeptide toxin that exhibits biological activity as an insecticide. The objective of this research was to produce polyclonal antibodies (Pabs) that could be used for the immunological quantification method in order to quantify of the production of beauvericin in seven (7) strains of B. bassiana (Bb) from the collection of Cenicafe-Colombia. Liquid cultures of Sabouraud "s medium were inoculated with 3,0 x 105 conidia/ml of each isolate and these extracts were filtered and evaluated at 7, 9 and 11 days of growth. Pabs were obtained through two intramuscular injections in New Zealand white rabbits. The injections contained 2,5 mg of the emulsified immunogen with f'reund's complete adjuvant for the first irtjection and with Freund's incomplete adjuvant for the second. The serological tests used in this experiment were ELISA and Dot-blot. The results showed differences in toxin production among seven isolates of the fungus B. bassiana. Ali isolations showed a peak of production between 9 and 1 1  days of culture. The levels of the beauvericin detected fluctuated between L 16 µ.g/¡,I for isolate B. bassiana 9610 and 1,57 µg / µl for isolate B. bassiana 9205. This methodology will permit selection of the strains most efficient in toxin production, which could be incorporated into integrated pest management programs.